Interferon‐induced degradation of the persistent hepatitis B virus cccDNA form depends on ISG20. (9th May 2021) - Stadler, Daniela; Kächele, Martin; Jones, Alisha N; Hess, Julia; Urban, Christian; Schneider, Jessica; Xia, Yuchen; Oswald, Andreas; Nebioglu, Firat; Bester, Romina; Lasitschka, Felix; Ringelhan, Marc; et al.
Abstract: Hepatitis B virus (HBV) persists by depositing a covalently closed circular DNA (cccDNA) in the nucleus of infected cells that cannot be targeted by available antivirals. Interferons can diminish HBV cccDNA via APOBEC3‐mediated deamination. Here, we show that overexpression of APOBEC3A alone is not sufficient to reduce HBV cccDNA that requires additional treatment of cells with interferon indicating involvement of an interferon‐stimulated gene (ISG) in cccDNA degradation. Transcriptome analyses identify ISG20 as the only type I and II interferon‐induced, nuclear protein with annotated nuclease activity. ISG20 localizes to nucleoli of interferon‐stimulated hepatocytes and is enriched on deoxyuridine‐containing single‐stranded DNA that mimics transcriptionally active, APOBEC3A‐deaminated HBV DNA. ISG20 expression is detected in human livers in acute, self‐limiting but not in chronic hepatitis B. ISG20 depletion mitigates the interferon‐induced loss of cccDNA, and co‐expression with APOBEC3A is sufficient to diminish cccDNA. In conclusion, non‐cytolytic HBV cccDNA decline requires the concerted action of a deaminase and a nuclease. Our findings highlight that ISGs may cooperate in their antiviral activity that may be explored for therapeutic targeting. SYNOPSIS: Hepatitis B virus deposits a covalently closed circular (ccc)DNA in the nucleus of infected cells to persist. Interferons can purge cccDNA from the nucleus by inducing deaminases and the nuclease ISG20 that modify and subsequently degrade cccDNA. Interferons promote APOBEC3A‐mediated deamination and degradation of transcriptionally inactive HBV cccDNA. APOBEC3A expression is essential, but on its own not sufficient to diminish HBV cccDNA. In addition to APOBEC3A, the interferon‐induced nuclease ISG20 is required for cccDNA decline. Interferon‐induced co‐expression of APOBEC3A and ISG20 results in cooperative cccDNA purging from infected cells. Abstract : Hepatitis B virus deposits a covalently closed circular (ccc)DNA in the nucleus of infected cells to persist. Interferons can purge cccDNA from the nucleus by inducing deaminases and the nuclease ISG20 that modify and subsequently degrade cccDNA.